Bibliometrics Analysis on “Role of Library in Supporting Knowledge Management” Published During 1999-2020 - Tupan, Tupan; Setiorini, Retno Asihanti (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
Libraries must play a role in knowledge management created by all academicians so that it can be used by anyone. This study analyzes publications about the role of libraries in supporting knowledge management. The data were obtained from the Scopus database. The retrieval technique is by entering the keywords "Knowledge Management" and "Library" with a publication year limitation between 1992-2020. The data obtained were then grouped based on the year of publication, publication source and type of literature. For keyword mapping, this study used VosViewer. The results of the analysis showed that research publications on the role of libraries in supporting knowledge management were mostly carried out in 2013 and 2016. Library Management is the journal that publishes the most literature related to this research object, there were 11 documents with a total of 185 citations, was in the form of articles. From the VosViewer mapping, it showed that there were four clusters. Research topics that were mostly carried out were knowledge management systems, knowledge management, libraries and information science, academic libraries, knowledge sharing, knowledge management models, librarians, research development management, information science, innovation, library services, and university libraries.